Anatomical fundamentals of mediastinoscopy - C. Camaño, Mario; A. Bergalli, Luis (Cirugía del Uruguay, 1971)
The paper describes briefly mediastinoscopie techniques and studies the anatomy of the mediastinum that can be explored through endoscopy. Its cell tissue has the structure of concentric cylinders; its weak areas used for displacement of the instrument employed thus making it possible to explore ganglionic chains.